Banks Fragility: Does It Matter To Diversify Their Income? A Cross-Countries Evidence - Amran, Nur Hazimah; Ahmad, Wahida (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2S1 (2022): Theme: Promoting Financial and Household Resilience, 2022)
Income diversification sounds like more invulnerable yet, it is not always the case. Income diversification in banking could be advantageous or disadvantageous. This is because at one hand, income diversification mitigates the risk exposure, and on the other hand, it exposes the banks to more vulnerable financial health. Using unbalanced panel data of cross-countries that spans from 2009 to 2018, the study aims (i) to investigate the factors that influence banks' fragility; (ii) to compare significant differences in banks' fragility levels between Islamic and conventional banks and; (iii) to assess the interaction effects of income diversification on the relationship between size and banks fragility. The study employs a random effect model with cluster standard error in order to rectify the heteroscedasticity and autocorrelation issues. The study discovers capital level, cost efficiency, credit risk and size are the driven factors for banks fragility. Higher capital level and credit risk hamper the banks fragility. Corroborating to the too-big-to-fail theory, larger banks are more exposed to vulnerable of banks fragility. Interestingly, it is proven that different level of income diversification interacts the relationship between size and banks fragility differently. It is proposed for smaller banks to less focus on diversifying their income. Instead, the smaller banks should focus on the traditional banking businesses in which, accepting deposits and providing financing. Meanwhile, the larger banks are proposed to follow portfolio theory by diversifying their income in order to mitigate the banks fragility exposure. Research paper Keywords: Bank, Diversification, Liquidity, Stability, Financial Risk Reference to this paper should be made as follows: Amran, N. H., & Ahmad, W. (2022). Banks Fragility: Does It Matter To Diversify Their Income? A Cross-Countries Evidence. Journal of Entrepreneurship, Business and Economics , 10 (2S1), 144–169